Mechanical and electrical support for MIDI auto saxophone - Muhammad Shukran, Zaini (2013)
Saxophone is most commonly associated with jazz and classical music. As the sound waves are produced by an oscillating reed, the saxophone is categorized as woodwind instruments. Different pitches from the saxophone are produced by opening and, closing keys. In order for a person to play the saxophone seamlessly, he or she need to have good respiratory control and fingering skills. Although fingering skills is much easier to be acquired compared to the respiratory control, but it still need a plenty of training and practices. As for the respiratory control, a saxophonist will have to control the volume and speed of the exhale air in order to produce a desired tone. In order to achieve that, the person should have good breath control and large lungs capacity. As conclusion from above, it is hard to develop a good saxophonist among us. The MIDI Auto Saxophone is a platform intended to be the replacement for the saxophonist for instance when a saxophonist is needed immediately. MIDI Auto Saxophone is one of the project that build autonomous device that .play musical instrument by means of conversion of the MIDI message file into digital signal and then being sent to air pressure control system and fingering system. This project is then intended to develop the mechanical and electrical support for the MIDI Auto Saxophone.